Kalahari.com : going places with the marketplace - Townsend, Stephanie; Dagada, Rabelani ([London] : SAGE, 2016)
In February 2010, online retail company Kalahari.com launched the Marketplace, a trading platform aimed at allowing third parties to use the Kalahari.com site to sell their goods. By May 2012, the success of the venture was exceeding expectations. Still, Bill Paladino, chief executive officer of the MIH Group, the South African multimedia company that owned Kalahari.com, knew that the competitive nature of the online retail industry meant that there was no room for complacency. He wondered how to ensure the continued success of the Marketplace.
Originally Published in: Townsend, S. & Dagada, R. (2012). Kalahari.com: Going Places with the Marketplace. WBS-2012-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Kalahari.com (Firm); Strategic planning -- Case studies; Electronic commerce -- Technological innovations -- Case studies; Electronic commerce -- Case studies